Experimental Study of Seepage Characteristics of Filling Structures in Deep Roadway - Shaoshuai Shi; Xiangxiang Zhu; Zhiguo Cao; Lin Bu; Zhijie Wen; Zongqing Zhou; Weidong Guo; Ruijie Zhao (Geofluids)
In order to study the seepage failure mechanism of roadway filling medium consisting of cohesive soil under complex hydrogeological conditions, a large-scale triaxial stress-seepage test system was utilized to investigate the influence of kaolin content and seepage loading rate on the seepage characteristics of filling medium. Through the analysis on the variation rules of sand loss and particle size distribution, the seepage characteristics and whole process of seepage instability of filling medium were explored in depth. It is concluded that (1) The seepage instability process of filling medium can be categorized into three stages: the initiation loss of fine clay, the accelerating loss of soil, and the stable status of soil loss. (2) The seepage failure process rate is proportional to the seepage loading rate and inversely proportional to the content of kaolin. (3) The kaolin and sand content of remaining mixture presented initial>bottom>middle>top status. The research results have guidance value for exploring the instability evolution mechanism of filling medium in deep roadway.